2020
DOI: 10.37766/inplasy2020.8.0018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guizhi decoction for diabetic cardiac autonomic neuropathy: a protocol for a systematic review and meta-analysis

Abstract: Review question / Objective: How effective is Guizhi decoction supplementation in the treatment of diabetic cardiac autonomic neuropathy? C o n d i t i o n b e i n g s t u d i e d : G u i z h i decoction.diabetic cardiac autonomic neuropathy. METHODS Participant or population: a) DCAN patients must meet the World Health Organization (WHO) "diabetes" diagnosis standard in INPLASY 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Additionally, we found that GZD significantly improved heart rate variability and vagus nerve activity, which are associated with the progression of hypertension [10]. A meta-analysis confirmed the beneficial effect and safety of GZD in the treatment of diabetic cardiac autonomic neuropathy [12]. Zheng et al reported that GZD associated formulas exerted significant effects on the attenuation of moderate-severe painful diabetic peripheral neuropathy [13].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Additionally, we found that GZD significantly improved heart rate variability and vagus nerve activity, which are associated with the progression of hypertension [10]. A meta-analysis confirmed the beneficial effect and safety of GZD in the treatment of diabetic cardiac autonomic neuropathy [12]. Zheng et al reported that GZD associated formulas exerted significant effects on the attenuation of moderate-severe painful diabetic peripheral neuropathy [13].…”
Section: Introductionsupporting
confidence: 64%
“…GZD is wildly used to treat many internal diseases, including allergic or respiratory diseases, endocrine system disease, nervous system disease, and cardiac autonomic neuropathy [25]. Additionally, GZD has accumulated plentiful experiences in the treatment of cardiovascular diseases, such as hypertension [11,12,26]. However, its material basis and potential mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%